Optimum fine and coarse aggregates proportions to produce strength of concrete - Danggang, Harry (University Malaysia Sarawak, (UNIMAS), 2000)
In this project, the mixture of concrete influenced by added quarry chip to produce strength of concrete are investigated. The research also includes tests and work-ability and compressive strength development.